Ecological Aspects of Mangroves in Poka Village, Inner Ambon Bay as a Basis for Management (Agrikan Jurnal Agribisnis Perikanan, 2024)
. The research was conducted in August-September 2024 in the Mangrove Ecosystem of Poka Village using the Belt Transect method on ten transects. From the research results, eight species of mangroves were found, namely Sonneratia alba, Sonneratia caseolaris, Bruguiera parviflora, Rhizophora apiculata, Rhizophora mucronata, Avicennia alba, Aegiceras corniculatum, and Aegiceras floridum, which belong to four families and five genera. Rhizophora apiculata has the highest density value in the tree, sapling, and seedling categories. The highest frequency of presence in the tree category is represented by Sonneratia alba, while Rhizophora apiculata represents the sapling and seedling categories. The lowest density and frequency of presence in the tree and seedling categories are represented by Aegiceras floridum, while Avicennia alba represents the sapling category. The highest species coverage value in the tree category is represented by Sonneratia alba, while Rhizophora apiculata represents the sapling category. Based on the Important Value Index (IVI), it is known that Sonneratia alba has the largest contribution or role in the mangrove ecosystem of Poka Village for the tree category, while Rhizophora apiculata represents the sapling category.
Keywords: Ecological; Mangrove; Poka